‘WHAT KIND OF MOTHER ARE YOU?!’ AI-supported psychological analysis of the phenomenon of online hate speech against women giving birth by caesarean section - Wioletta Tuszyńska-Bogucka; Katarzyna Bosowska (Journal of Modern Science)
Objectives In recent years, Poland has seen the emergence of online hate speech against women giving birth by caesarean section. This phenomenon appears to warrant exploration, given the negative impact it may have both on women who have already given birth in this way and on those who are about to choose how to give birth.